DEVELOPING A DIGITAL TRANSFORMATION PROCESS IN THE MANUFACTURING SECTOR: EGYPTIAN CASE STUDY - Abdallah, Yasser Omar; Shehab, Essam; Al-Ashaab, Ahmed (Information Systems and e-Business Management, 2022)
Digital transformation is of crucial importance in the manufacturing industry, especially after the COVID-19 pandemic because of the increasing need for remote working and socially distanced workplaces. However, there is a lack of a clear and well-defined process to implement digital transformation in manufacturing. This paper aims to identify the most critical stages to implementing digital transformation in the manufacturing sector. Twenty-one structured interviews with experienced specialists in digitalisation in the manufacturing sector in the Egyptian economy were held and used the Best–Worst Method to analyse the data as an analysis tool for a multiple criteria decision making (MCDM) approach. The digital transformation process comprises eight stages covering technology, management, communications, and customer elements. The main contribution of this work stage is the balance between the different elements of digital transformation—digital technologies, leadership and strategy, people and business processes—to create an integrated 8-step process of digital transformation in the manufacturing sector of developing economies such as the Egyptian economy.
Keywords: Type of access: Open Access; Digital transformation; Manufacturing; Digitalisation; Digital process; Multiple Criteria Decision Making (MCDM)